Strategic aspects of fighting in alliances - Kai A. Konrad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
This paper surveys some of the strategic aspects that emerge if players fight in an alliance against an enemy. The survey includes the free-rider problem and the hold-up problem that emerges in the baseline model, the role of supermodularity in alliance members' effort contributions, the role of budget constraints, the role of information transfer inside the alliance, and the role of in-group favoritism.
Keywords: D72; D74; 330; Alliances; contests; conflict; in-group favoritism